Literatur Review Pengaruh Latihan Gerak Pinggul Terhadap Penurunam Intensitas Nyeri Punggung Bawah Pada Lansia - Karina Indana Zulfa; Feriana Ira Handian; Achmad Dafir Firdaus (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Introduction: The prevalence of back pain is a lot of complaints by the public, especially in the elderly aged 55 years and over. The high rate of recurrence and pain complaints that are often felt by the general public, especially in the elderly, shows that the treatment and management of lower back pain complaints has not been completely resolved. The purpose of this study was to explain the effect of hip movement exercises on decreasing the intensity of lower back pain. Method: The method used in this study is a literature review using 4 search databases, namely PubMed, Proquest, Science Direct and Google Scholar. The inclusion criteria in this study were journals for the last 5 years with quality assessment using the PICOS framework (Population, Intervention, Comparation, Outcome, Study Design). Result: The results showed that from 11 journals that had been analyzed, there were 10 journals (91%) which stated that stretching exercises had an influence in dealing with low back pain and 1 journal (9%) stated that there was no effect. Conclusion: The application of hip movement exercises (stretching) can affect the decrease in the intensity of low back pain felt by the elderly, where stretching exercises can reduce the feeling of muscle stiffness and improve joint flexibility felt by the elderly. Recommendation: Health workers, especially nurses, can teach or implement this intervention to overcome low back pain.